The prevalence of childhood sexual experiences and intimate partner violence among transgender women in China: Risk factors for lifetime suicidal ideation - Xu, Lulu; Chang, Ruijie; Chen, Yingjie; Xia, Danni; Xu, Chen; Yu, Xiaoyue; Chen, Hui; Wang, Rongxi; Liu, Yujie; Liu, Shangbin; Ge, Xin; Ma, Tiecheng; et al. (Frontiers in Public Health, 2023)
Objective Several studies highlighted childhood sexual experiences (CSEs) and intimate partner violence (IPV) as risk factors that affected lifetime suicidal ideation. TW had higher rates of CSEs and IPV than cisgender people. The aim of this study was to comprehensively assess the prevalence of CSEs and IPV among TW and their association with lifetime suicidal ideation. Methods A cross-sectional survey was conducted among 247 TW in Shenyang and Kunming, China, from April to September 2018. CSEs, IPV, and lifetime suicidal ideation were assessed. Logistic regression models were used to examine the association between self-reported CSEs under 18 years of age, IPV in adulthood, and lifetime suicidal ideation. Results In the study, 14.2% (35/247) of the sample participants reported CSEs under 18 years of age; 44.9% (111/247) reported experiencing IPV in adulthood, including 18.6% (44/247) of physical IPV, 27.1% (67/247) of trans-specific identity IPV, 31.6% (78/247) of verbal IPV, and 19.4% (48/247) of sexual IPV; and 26.3% (65/247) had thought about attempting suicide at least one time. CSEs and any form of IPV were significantly associated with suicidal ideation in this sample population. A final stepwise multivariate logistic regression model found that both physical and verbal IPVs were significantly associated with suicidal ideation when controlling for other factors (ORm1 = 2.58, 95% confidence interval (CI) = 1.163–5.724; ORm2 = 2.72, 95% CI = 1.334–5.547). Conclusions The findings highlight the effects of CSEs and IPV among TW and suggest the need for research on suicide in the future. Suicide prevention efforts for this invisible and vulnerable population should focus on those with physical and verbal IPV.